Validity and reliability of a wearable armband for continuous sweat conductivity monitoring during exercise - Ferrari, A.; Ratel, S.; Berthoin, S.; Garnier, J.-P.; Baquet, G. (Frontiers in Physiology, 2026)
Introduction: Sweating is essential for thermoregulation during exercise but causes variable losses of water and sodium chloride (NaCl). Field-based methods to assess these losses are limited by sampling errors and the lack of real-time feedback. This study evaluated the validity and reliability of the BeOne armband for continuous measurement of sweat conductivity, used to estimate sweat [NaCl] equivalent in real time.